Keterkaitan Nilai Tukar Dengan Ekonomi Internasional Relevansi The Foreign Exchange Market - Sintia Melati; Diana Asri Fitri Sinaga; Firli Safitri; Viktor Manurung; Hafiza Adlina (Penerbit Yayasan Daarul Huda Kruengmane, 2023)
The exchange rate reflects the strength of the country's economy. When the country's economy is dominated by a weakening currency. The development of the amount of money circulating in Indonesia is effectively influenced by people's behavior and the steps taken by the government. As a result, monetary developments in Indonesia are more dynamic. The main function of the currency market, according to Sercu, is to ensure the transfer of money from one country to another and the conversion of currency to other countries.